2019
DOI: 10.1002/osi2.1000
|View full text |Cite
|
Sign up to set email alerts
|

Oral and dental health of Italian drug addicted in methadone treatment

Abstract: Objectives Our group recorded the characteristic of oro‐dental health among a group of drug addicts in recovery treatment with methadone, and it evaluated the changes related to the withdrawal therapy. Methodology A sample of 50 drug addicts in treatment with methadone was included in this study. At the beginning of the withdrawal therapy, the authors recorded the parameters involved in the most common oral diseases. Moreover, it was evaluated how, during the rehabilitation protocol, the behavioral parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In the first focus area, 23 studies were identified that included 3611 participants with a mean age ranging from 27.9 to 44 years [ 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The studies were conducted in Australia ( n = 2), Brazil ( n = 3), India ( n = 2), Indonesia ( n = 1), Iran ( n = 1), Ireland ( n = 2), Italy ( n = 2), Lithuania ( n = 1), Norway ( n = 1), Portugal ( n = 1), Serbia ( n = 1), South Africa ( n = 1), United Kingdom ( n = 1) and the United States ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first focus area, 23 studies were identified that included 3611 participants with a mean age ranging from 27.9 to 44 years [ 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The studies were conducted in Australia ( n = 2), Brazil ( n = 3), India ( n = 2), Indonesia ( n = 1), Iran ( n = 1), Ireland ( n = 2), Italy ( n = 2), Lithuania ( n = 1), Norway ( n = 1), Portugal ( n = 1), Serbia ( n = 1), South Africa ( n = 1), United Kingdom ( n = 1) and the United States ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in Australia ( n = 2), Brazil ( n = 3), India ( n = 2), Indonesia ( n = 1), Iran ( n = 1), Ireland ( n = 2), Italy ( n = 2), Lithuania ( n = 1), Norway ( n = 1), Portugal ( n = 1), Serbia ( n = 1), South Africa ( n = 1), United Kingdom ( n = 1) and the United States ( n = 4). About half of the studies were of cross‐sectional design ( n = 14) [ 32 , 33 , 35 , 36 , 39 , 40 , 41 , 43 , 46 , 47 , 48 , 50 , 51 , 52 ]; few studies used a qualitative design ( n = 3) [ 19 , 38 , 53 ]; and the designs of remaining six studies were cohort ( n = 3) [ 42 , 44 , 45 ], case–control ( n = 1) [ 34 ], prospective longitudinal ( n = 1) [ 49 ] and pre‐post quasi‐experimental ( n = 1) [ 37 ]. In the second focus area, the guidelines identified were developed for application in Australia ( n = 2), Canada ( n = 2), Ireland ( n = 1), United Kingdom ( n = 1) and the United States ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, poor appearance and improper functioning of the dental problems can cause isolation and non-compliance with the treatment and care process (9). So far, few studies were conducted on oral health and its related quality of life among the addicts worldwide (10)(11)(12) and in Iranian cities of Yazd, Mashhad, Isfahan, and Tehran (19 − 13). Some of these studies concluded that drug abuse increased DMFT and Plaque Control Record indices (14).…”
Section: Introductionmentioning
confidence: 99%